2000
DOI: 10.1002/1099-0518(20001201)38:23<4206::aid-pola60>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of butyl acrylate-styrene block copolymers in emulsion by reversible addition-fragmentation chain transfer: Effect of surfactant migration upon film formation

Abstract: The synthesis of block copolymers in an environmentally friendly medium was carried out in emulsion polymerizations through the reversible addition‐fragmentation chain transfer process, using a transfer active xanthate (MADIX) agent, under batch and starved‐feed conditions. First, ab initio experiments were carried out to prepare a seed of PBA dormant chains (i.e., poly(butyl acrylate) (PBA) polymer attached with a transfer active xanthate). The M̄n and polydispersity were predicted accurately with numerical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(148 citation statements)
references
References 17 publications
(17 reference statements)
6
141
1
Order By: Relevance
“…[9] Much research has shown that the success in RAFT emulsion polymerization depends strongly on the choice of RAFT agent and polymerization conditions. [9,[175][176][177][178][179][180][181][182][183] Most work has focussed on styrene polymerization, [9,176,177,183] although RAFT emulsion polymerizations of BA [178] and methcrylates [9,13] have also been reported. Use of cumyl dithiobenzoate 22 as RAFT agent in ab initio emulsion polymerization of styrene is not recommended.…”
Section: Raft In Heterogeneous Mediamentioning
confidence: 99%
“…[9] Much research has shown that the success in RAFT emulsion polymerization depends strongly on the choice of RAFT agent and polymerization conditions. [9,[175][176][177][178][179][180][181][182][183] Most work has focussed on styrene polymerization, [9,176,177,183] although RAFT emulsion polymerizations of BA [178] and methcrylates [9,13] have also been reported. Use of cumyl dithiobenzoate 22 as RAFT agent in ab initio emulsion polymerization of styrene is not recommended.…”
Section: Raft In Heterogeneous Mediamentioning
confidence: 99%
“…Since then, significant effort has been devoted to these new versatile approaches towards controlled polymer synthesis, including the development of dithiocarbamate controlling agents, [9,10] novel controlled homopolymers like poly-(acrylic acid) [11] and block copolymers, [12] and the first successful applications in dispersed media. [13,14] O-Ethyl xanthates of the general structure R-S(C S)-OEt (X 1-8 ) with varying substituents R have been synthesized and used for the thermal bulk radical polymerization of styrene. The present study deals with the influence of the nature of the leaving group R on the level of control of the polymerization of styrene (St).…”
Section: Introductionmentioning
confidence: 99%
“…This temperature has been selected in view of a future extension to MADIX emulsion polymerization. 33,74,75 Moreover, the self-initiation of styrene is suppressed, simplifying the overall kinetic description. 76 Temperature control was possible through in situ measurements via a thermocouple inserted in the rubber septum.…”
Section: Madix Synthesis Proceduresmentioning
confidence: 99%